Checklist of the Freshwater Fishes of Argentina. 2nd edition. (CLOFFAR-2) - Mirande, Juan Marcos (2020)
The purpose of this paper is to present an updated list of fishes found in Argentina’s freshwaters based on the available literature. Since the last list, CLOFFAR by Mirande & Koerber, was published in 2015, most systematical and distributional changes were presented on www.pecescriollos.de and six updates have been published (Koerber et al. 2015, 2016, 2017a, 2017b, 2018, 2019).